Pengalaman Rasa Nyeri Dan Pengekspresiannya Pada Pasien Pasca Operasi - Mayangsari, Intan; Setia Asyanti, S. Psi, M.Si (2016)
ABSTRACT The painfull expression is called painfull response is a complex phenomena include with the sensoric, behavior or motoric, emotion even the cultures of individual differences. The research was purposed to know how the pain expression and their experience to surgecial operations patients. The informan of this research have many characteristic, they are : a). surgecial operations patients in Karima Utama Hospital who had done major surgery b) the patient with many kinds age, they are teenagers, adults, and elderlies. c) the patient with the broken bones and tumor. This research use structured interview, observation, answer the painfull scale, and thematically analyzed. The result showed that the patients will moan, frowned, complaining, straching, keep silence, crying, give some massage or touch to pain body for express their pain but also just a little patient only be silent when feel the pain. And then, we can know that this painfull disturb the daily life of the patient because the informan need helps to do activity in everyday, for example eat, take a bath and the others. This research can use consideration to informan so they don't doing activity that exhausted the energy, break enough and make sure that painfull's medicine has already. Beside that, all family have to accompany and make calm emotional patient when the informan feeling pain. Keywords : expression, feeling pain, surgecial operations patients